One Health approach to hemotropic mycoplasmas (hemoplasmas): Molecular detection in quilombola communities and their dogs in Brazil - Louise Bach Kmetiuk; Paul Shaw; Ashley Wallington; Giovanni Kalempa Panazzolo; Orlei José Domingues; Jobin Jose Kattoor; Mathew Johnson; Lendro Meneguelli Biondo; Rebecca Wilkes; Fabiano Borges Figueiredo; Giovani Marino Fávero; Joanne B. Messick; et al. (One Health)
Hemoplasmas (hemotropic mycoplasmas) are obligatory red blood cell bacteria that may infect and cause anemia in several mammalian species. IAccordingly, the present study assessed four quilombola communities during six on-field expeditions between December 2021 and March 2022 in the central-eastern Paraná State, southern Brazil. Overall, 12/208 (5.8 %) quilombola individuals were positive for hemoplasma infection by qPCR. Results of 16S ribosomal RNA gene sequencing confirmed Mycoplasma heamocanis infection in two human samples. In addition, hemoplasma infection was detected by qPCR in 19/100 (19.0 %) dogs including 16/19 (84.2 %) dogs for Candidatus Mycoplasma haematoparvum, 7/19 (3.7 %) for M. haemocanis, and 4/19 (21.0 %) for both. To the author's knowledge, this is the first One Health approach study of hemoplasma detection in quilombola individuals along with their dogs as vulnerable populations worldwide, with M. heamocanis detection in both human and companion animals.